"Quo Vadis" Oncologic Hyperthermia?. (8th September 2013) - Szasz, Andras
Abstract : Hyperthermia was the very first oncotherapy in human medicine based directly on sacral and philosophical roots in ancient cultures. The discovery of electromagnetism gave new hopes a century ago; however, up to now it has been suffering from lack of wide applications. Oncological hyperthermia struggles with multiple technical and medical problems which are far from the complete solution. Technically, the deep heating, the precise focusing, the technical control, and repeatability are challenging. The missing medical explanation of the phenomenon, together with the he missing measurable dose hinders the acceptance of hyperthermia. The contra-feedback of physiology mechanisms makes this method hardly controllable. Multiple, most promising results and studies are mixed together with some negatives and controversial consequences, causing huge fluctuations of its applications. There are positive and negative "believers" of the method, but the decisional facts are missing. A new way gives shape to the development: heating in nanorange, which could solve most of the open problems in oncological hyperthermia.